2017
DOI: 10.1002/hbm.23575
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐task diagnosis for autism spectrum disorders using multi‐modality features: A multi‐center study

Abstract: Autism spectrum disorder (ASD) is a neurodevelopment disease characterized by impairment of social interaction, language, behavior and cognitive functions. Up to now, many imaging-based methods for ASD diagnosis have been developed. For example, one may extract abundant features from multi-modality images and then derive a discriminant function to map the selected features toward the disease label. A lot of recent works, however, are limited to single imaging centers. To this end, we propose a novel multi-moda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…However, because it is difficult to recruit representative populations of stimulant‐naïve ADHD adults from a single‐site, larger ML‐based studies combining data from multiple sites (obtained with the same selection criteria) may be considered as a more feasible alternative . Such multi‐site MRI studies should allow both the testing of diagnostic performance across independent validation samples of adults never treated for ADHD symptoms , and the use of novel multi‐task learning methods suitable for finding disease‐related signatures while handling heterogeneity across different populations and MRI acquisition protocols .…”
Section: Discussionmentioning
confidence: 99%
“…However, because it is difficult to recruit representative populations of stimulant‐naïve ADHD adults from a single‐site, larger ML‐based studies combining data from multiple sites (obtained with the same selection criteria) may be considered as a more feasible alternative . Such multi‐site MRI studies should allow both the testing of diagnostic performance across independent validation samples of adults never treated for ADHD symptoms , and the use of novel multi‐task learning methods suitable for finding disease‐related signatures while handling heterogeneity across different populations and MRI acquisition protocols .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [9,10] proposed a multitask deep learning method for diagnosing Alzheimer's Disease by combining MRI, PET, and Assessment Scale-Cognitive subscale (ADAS-Cog) with the restricted Boltzmann machine. Wang et al [11] explained a novel multimodality multicenter classification method for autism spectrum disorder diagnosis; they regarded the classification of each imaging center as one task and solved the classification for all imaging centers by introducing the task-task and modality-modality regularizations. Liu et al [12] proposed a view-aligned hypergraph learning (VAHL) method and utilized incomplete multimodality data for AD/MCI diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that there were 62.2 million ASD cases in the world in 2015 [1]. However, the pathological mechanism of ASD is unclear, and conventional diagnosis of ASD is usually based on symptoms [2], and thus the precise diagnosis is the main challenge in the research literature of ASD.…”
Section: Introductionmentioning
confidence: 99%